Cover cropping system and mulching can shape soil microbial status in fruit orchards (Scientia Agricola, 2020)
The use of cover crop in agricultural fields has been well elucidated, especially regarding nitrogen fixation from legume crops and their function as weed protection. Furthermore, to cover crops can benefit the soil microbial community. This study aimed to evaluate and compare the benefits of mulching and cover cropping systems on soil microbial growth and activity, and their effects on plant mineral nutrition in pomelo (Citrus maxima) and macadamia (Macadamia integrifolia) orchards. The treatments included: 1) control [Glyphosate herbicide (Roundup at 4 l per ha)], 2) manual weed control, 3) mulching with dead leaves from their respective trees (macadamia and pomelo), 4) millet, 5) faba bean, 6) millet + faba bean. All the treatments were applied for 120 days before soil and plant leaves were sampled for analyses. Plant mineral nutrition, soil microbial biomass C (MBC) and soil microbial biomass N (MBN); basal respiration (BRA), arbuscular mycorrhizal fungi (AMF) colonization (COL); number of AMF spores (SPO) in soil; total organic carbon (TOC) and total nitrogen (TN) were evaluated. Plant nutrition was not altered by the treatments; however, the MBC, COL and SPO markedly increased in response to mulching and faba bean + millet treatments. Especially in macadamia soils, these treatments had a great response to soil microbiology. Significant negative correlations were also detected for the COL, SPO, BRA and TOC with the Nutrient Balance Index (NBI). These results indicate that in short-term the cover cropping system is useful to improve the soil microbial growth and AMF formation in soils of pomelo and macadam orchards.